Lats-IN-1 protects cardiac function and promotes regeneration after myocardial infarction by targeting the hippo pathway - Shen, Hua; Wang, Qing; Liu, Bohan; Wang, Yihui; Zhou, Dandan; Zhang, Lin; Zhuang, Jinqiang (Frontiers in Pharmacology, 2024)
In this study, we explored the efficacy of Lats-IN-1, a LATS1/2 kinase inhibitor that targets the Hippo pathway, as a novel treatment for myocardial infarction (MI), a leading cause of heart failure globally due to the loss of cardiomyocytes. Using male C57BL/6 mice subjected to surgically induced MI, we treated these models with Lats-IN-1 and assessed cardiac function, infarct size, cardiomyocyte proliferation, and apoptosis. Our findings demonstrate that Lats-IN-1 significantly improves cardiac function, evidenced by enhanced ejection fraction and reduced ventricular dimensions, alongside a notable decrease in infarct size and apoptosis rates. Furthermore, it increased cardiomyocyte proliferation, indicating its potential to promote cardiac repair and regeneration. By modulating the Hippo pathway and reducing apoptosis markers, Lats-IN-1 emerges as a promising therapeutic strategy for improving outcomes in heart diseases marked by cardiomyocyte loss, underscoring the critical role of the Hippo pathway in cardiac regeneration.